2016
DOI: 10.1111/mcn.12418
|View full text |Cite
|
Sign up to set email alerts
|

Maternal plasma cholesterol and duration of pregnancy: A prospective cohort study in Ghana

Abstract: Low plasma cholesterol may be associated with preterm birth; however, results are mixed and limited primarily to high‐income countries. Our objective was to determine whether maternal plasma lipid concentrations are associated with pregnancy duration. We performed a nested cohort (n = 320) study of pregnant Ghanaian women enrolled in a randomized controlled trial. Total cholesterol, high‐density lipoprotein cholesterol (HDL‐C), low‐density lipoprotein cholesterol, and triglyceride concentrations were analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 48 publications
2
8
3
Order By: Relevance
“…These findings suggest that dietary interventions to improve diet and increase cholesterol levels during pregnancy may promote fetal growth and reduce adverse birth weight-related outcomes. Consistent with previous studies, we observed an increase in plasma TC, LDL-c and TG levels across pregnancy [10,16,17,26,27], which is known to be part of a normal physiological response to gestation [28]. However, unlike in studies from higher-income countries [10,27,28], our data show a decrease in HDL-c levels from 20 to 30 weeks gestation, following an initial rise across the first half of pregnancy.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These findings suggest that dietary interventions to improve diet and increase cholesterol levels during pregnancy may promote fetal growth and reduce adverse birth weight-related outcomes. Consistent with previous studies, we observed an increase in plasma TC, LDL-c and TG levels across pregnancy [10,16,17,26,27], which is known to be part of a normal physiological response to gestation [28]. However, unlike in studies from higher-income countries [10,27,28], our data show a decrease in HDL-c levels from 20 to 30 weeks gestation, following an initial rise across the first half of pregnancy.…”
Section: Discussionsupporting
confidence: 90%
“…In this cohort of pregnant women from rural Gambia, plasma lipid levels were lower compared to those reported in studies from high-income countries [26][27][28][29] or urban areas in LMICs [30], likely reflecting the typical diet in rural Gambia which is low in animal-source foods and consists mainly of carbohydrate-rich staple foods. Low HDL-c levels in the first half of pregnancy were associated with three times the risk of LBW.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…In the United States, low maternal HDL cholesterol (HDL-C) was associated with a low birth weight z-score, 10 and in Ghana, we previously reported that high HDL-C at 36 weeks gestation was positively associated with the duration of gestation. 11 Even less is known about HDL particles, particularly in infants; however, limited evidence in preterm infants indicates that a lower concentration of HDL particles is found in infants with chronic lung disease compared to those without lung disease. 12 HDL particles display a variety of immunomodulatory capabilities, 13 including boosting the ability of innate immune cells to fight infection, 14 and may thus be particularly important in settings with high infection burden.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Very little is known about the role of HDL during pregnancy and in early development. In the United States, low maternal HDL cholesterol (HDL-C) was associated with a low birth weight z-score, and in Ghana, we previously reported that high HDL-C at 36 weeks gestation was positively associated with the duration of gestation . Even less is known about HDL particles, particularly in infants; however, limited evidence in preterm infants indicates that a lower concentration of HDL particles is found in infants with chronic lung disease compared to those without lung disease .…”
Section: Introductionmentioning
confidence: 99%